Intracerebral Hemorrhage in Eclampsia - Ye. M. Shifman (Общая реаниматология, 2008)
The classical triad of symptoms is a basis for making the diagnosis of eclampsia. Nevertheless, none pregnancy complication fails to differ in clinical manifestations, the uncertainty and ambiguity of maternal and fetal prognosis, and in the direct causes of fatal outcomes. The authors present an account of a case of maternal mortality. A 17-year-old primigravida with a history of arterial hypertension at gestational weeks 31—32 developed a series of seizures and lost consciousness. She was diagnosed as having eclampsia complicated by acute ischemic attack. Emergency cesarean delivery was made. Postoperatively, the puerpera was transferred to the neurosurgery unit to be examined and treated. Computed tomography revealed intracerebral hemorrhage, with blood entering the brain ventricles, and occlusive hydrocephalus from the fourth ventricular level. Ventricular drainage was made as described by Arendt. The prognosis was poor. The patient’s death was stated on postpartum day 5. The authors consider that the publication and discussion of such cases should give a better insight into the development of eclampsia and its life-threatening complications. Fortunately, eclampsia is rare, the incidence of its complications is even less. But each such a case deserves a detailed and thoughtful discussion. Key words: eclampsia, intracerebral hemorrhage.